Self-Identity Management and Branding on Social Media: A Case Study of WhatsApp Status through the Johari Window Perspective - Machsunah, Uun (Jurnal Polisci, 2025)
This study aims to examine self-identity management and branding on social media with a focus on WhatsApp status, using the Johari Window four-quadrant theory approach, functioning to express themselves openly, blindly, hidden, and unknowingly. Data were collected through interviews and content analysis of informants' WhatsApp statuses. The informants in this study consisted of four people with different backgrounds: a housewife, a lecturer, a writer, and a lecturer and preacher. The results showed that each informant had a unique way of managing their identity and self-branding through WhatsApp status. The first informant, a housewife, actively shares her activities on social media, including videos of singing with interesting face filters. She shows open and hidden identities, with satirical statuses reflecting the blind self-aspect, while in the open quadrant the expression of happiness reflects positive self-branding. The second informant, a lecturer, posts social and teaching activities, creating an image as an active and accomplished individual. Also statuses related to culinary and vacations show personal well-being, reflecting hidden identities. The third informant, a writer, brands himself as a writing service provider with consistency in posting writing activities. The cursing status shows a blind self, where the negative impact of the reaction may not be realized. The fourth informant, a lecturer and preacher, posts tausiyah and songs, creating an image as a religious individual and a positive influence. This study highlights how each informant uses WhatsApp status to build self-identity and branding, and how aspects of the Johari Window theory can help understand these dynamics. All four informants revealed that they use WhatsApp status to strengthen their self-image and personal branding, by considering the audience who will see the status. In addition, this study found that social interaction and feedback from friends on WhatsApp play an important role in the process of self-identity management. This study contributes to the understanding of how individuals manage their identities in the digital era and the importance of social media in shaping public perceptions of themselves.